2017
DOI: 10.3847/1538-3881/aa74cd
|View full text |Cite
|
Sign up to set email alerts
|

An Upper Limit on the Mass of the Circumplanetary Disk for DH Tau b*

Abstract: DHTau is a young (∼1 Myr) classical TTauri star. It is one of the few young PMS stars known to be associated with a planetary mass companion, DHTaub, orbiting at large separation and detected by direct imaging. DHTaub is thought to be accreting based on copious a H emission and exhibits variable Paschen Beta emission. NOEMA observations at 230 GHz allow us to place constraints on the disk dust mass for both DHTaub and the primary in a regime where the disks will appear optically thin. We estimate a dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
2
29
1
Order By: Relevance
“…Compact dust continuum emission is optically thick, rather than optically thin as usually assumed. We note that similar thoughts have been discussed and applied to derive an upper limit on disk size MacGregor et al 2017;Ricci et al 2017;Wolff et al 2017). Here, we further study the brightness and implications of compact optically-thick disks.…”
Section: Compact Optically-thick Disksupporting
confidence: 54%
“…Compact dust continuum emission is optically thick, rather than optically thin as usually assumed. We note that similar thoughts have been discussed and applied to derive an upper limit on disk size MacGregor et al 2017;Ricci et al 2017;Wolff et al 2017). Here, we further study the brightness and implications of compact optically-thick disks.…”
Section: Compact Optically-thick Disksupporting
confidence: 54%
“…Paβ emission was not observed in the moderate-resolution spectroscopy of GQ Lup B presented by McElwain et al (2007) and Lavigne et al (2009), which suggests that the emission observed by Seifahrt et al (2007) was variable. Similarly, Wolff et al (2017) also found variable emission for DH Tau B. This suggests that other companions without Paβ emission could be observed during a quiescent state of low accretion.…”
Section: How Common Is Paβ Emission?mentioning
confidence: 72%
“…This observation is in good agreement with models of magnetic coupling between the planet and its circumplanetary disk (Takata & Stevenson 1996;Batygin 2018), which predict that this mechanism should provide an efficient means of angular momentum dissipation. Interestingly, previous studies have found active accretion signatures for DH Tau b, suggesting that it may still possess a cicumplanetary gas disk (Zhou et al 2014;Bonnefoy et al 2014;Wolff et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…In this model, the disk extracts angular momentum from the planet, while meridional circulation of gas within the Hill sphere recycles this angular-momentum rich gas back into the circumstellar nebula, thereby decreasing the planet's rotation rate. In fact, there is indirect evidence that DH Tau b is actively accreting, as this object has both Hα and Paβ emission lines in its spectrum (Zhou et al 2014;Bonnefoy et al 2014;Wolff et al 2017). This accretion would presumably be mediated via a circumplanetary gas disk, but Wu et al (2017) did not find any evidence for such a disk when they observed this object with ALMA.…”
Section: Angular Momentum Evolutionmentioning
confidence: 98%